Angiotensin‐converting enzyme inhibitor works as a scar formation inhibitor by down‐regulating Smad and TGF‐β‐activated kinase 1 (TAK1) pathways in mice - Tan, Wei‐Qiang; Fang, Qing‐Qing; Shen, Xiao Z; Giani, Jorge F; Zhao, Tuantuan V; Shi, Peng; Zhang, Li‐Yun; Khan, Zakir; Li, You; Li, Liang; Xu, Ji‐Hua; Bernstein, Ellen A; et al. (British journal of pharmacology, 2018)
Background and Purpose Angiotensin‐converting enzyme (ACE), an important part of the renin‐angiotensin system, is implicated in stimulating the fibrotic processes in the heart, lung, liver and kidney, while an ACE inhibitor (ACEI) promotes physiological tissue repair in these organs. The mechanism is closely related to TGF‐β1 pathways. However, the reported effects of applying ACEIs during scar formation are unclear. Hence, we explored the anti‐fibrotic effects of an ACEI and the molecular mechanisms involved in a mouse scar model. Experimental Approach After a full‐thickness skin wound operation, ACE wild‐type mice were randomly assigned to receive either ramipril, losartan or hydralazine p.o. ACE knockout (KO) mice and negative control mice only received vehicle (water). Wound/scar widths during wound healing and histological examinations were recorded at the final day. The ability of ACEI to reduce fibrosis via TGF‐β1 signalling was evaluated in vitro and in vivo. Key Results ACE KO mice and mice that received ramipril showed narrower wound/scar width, reduced fibroblast proliferation, decreased collagen and TGF‐β1 expression. ACEI attenuated the phosphorylation of small mothers against decapentaplegic (Smad2/3) and TGF‐β‐activated kinase 1 (TAK1) both in vitro and in vivo. The expression of ACE‐related peptides varied in murine models with different drug treatments. Conclusions and Implications ACEI showed anti‐fibrotic properties in scar formation by mediating downstream peptides to suppress TGF‐β1/Smad and TGF‐β1/TAK1 pathways. These findings suggest that dual inhibition of Smad and TAK1 signalling by ACEI is a useful strategy for the development of new anti‐fibrotic agents.